2014
DOI: 10.1177/1352458514523692
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic thrombocytopenic purpura-hemolytic uremic syndrome in relapsing-remitting multiple sclerosis patients on high-dose interferon β

Abstract: Three women aged 34-47 years old, on high dose interferon beta-1a for relapsing-remitting multiple sclerosis, were hospitalized between 2009-2012 for thrombotic thrombocytopenic purpura-hemolytic uremic syndrome. Patients sought medical attention for neurological symptoms including cephalalgia, blurred vision, confusion, focal deficits and seizures. All patients presented thrombocytopenia, hemolytic anemia and arterial hypertension. Despite plasma exchanges, corticosteroids and anti-CD20 treatments, all patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 8 publications
2
25
1
1
Order By: Relevance
“…Cessation of interferon might resolve TMA in some patients, and PE has been effective in controlling TMA in other patients. Serious cases might require continuation of dialysis therapy [6][7][8][9]. Similar clinical courses have also been reported for tacrolimus in patients with organ transplantation [19,20].…”
Section: Case Reportsupporting
confidence: 63%
See 4 more Smart Citations
“…Cessation of interferon might resolve TMA in some patients, and PE has been effective in controlling TMA in other patients. Serious cases might require continuation of dialysis therapy [6][7][8][9]. Similar clinical courses have also been reported for tacrolimus in patients with organ transplantation [19,20].…”
Section: Case Reportsupporting
confidence: 63%
“…A renal biopsy was not performed. Along with his clinical course, we concluded that this patient had possible TMA that was triggered by interferon b-1b administrated to treat MS, which was complicated by PRES through significant amplification of RAS by TMA in the kidney [6].…”
Section: Case Reportmentioning
confidence: 88%
See 3 more Smart Citations